Processing remotely sensed data for geological content over a part of the Barberton Greenstone Belt, Republic of South Africa. - Cloete, Derik (My University, 1993)
Various methods and techniques developed by researchers worldwide for enhancement and processing ATM, MSS· and TM remotely sensed data are tested. on LANDSAT 5 Thematic Mapper data from a part of the Barberton Greenstone Belt straddling the border between the Republic of South Africa and the Kingdom of Swaziland. Various enhancement techniques employed to facilitate the extraction of structural features and lineaments, and the findings Of the ensuing photogeologlcal interpretation are compared with existing geological maps~ Methods for the detection of zones of hydrothermal alteration. are also considered. The reflectance from vegetation, both natural and cultivated, and the possible reduction of the interference caused by this reflectance, are considered in detail. Partial unmixing of reflectances through the use of various methods and techniques, some of which are readily available from the literature, are performed and its effectiveness tested. Since large areas within the study area are covered by plantations, the interfereiice from the two types of vegetation present (i.e. natural and cultivated), were initially considered separately. In an attempt to isolate the forested areas from the natural vegetation, masks derived through image classification were used to differentially enhance the various features. Results indicate that the use of any particular method to the exclusion of all others will seriously limit the scope of conclusions possible through interpretation of the information present. Enhancement of information in one domain will inadvertently lead to the suppression of information from one or more of the coexisting domains. A series of results from a sequence of procedures interpreted in parallel will in every case produce information of a higher decision making quality.
Keywords: Geology -- South Africa -- Barberton.